Improvement effects of a novel Chinese herbal formula in imiquimod and IL-23-stimulated mouse models of psoriasis - Lan Wang; Yao-Xing Dou; Qiu-Xia Yu; Zhen Hu; Siu-Po Ip; Yan-Fang Xian; Zhi-Xiu Lin (BMC, 2024)
Abstract Background Psoriasis is a long-term inflammatory skin disease. A novel herbal formula containing nine Chinese herbal medicines, named Inflammation Skin Disease Formula (ISDF), has been prescribed in clinics for decades. Aims To investigate the efficacy and action mechanisms of ISDF on psoriasis using imiquimod (IMQ) and Interleukin-23 (IL-23)-induced models in mice and reveal the pharmacokinetics profile of ISDF in rats. Methods Topical administration of IMQ and intradermal injection with IL-23 respectively induced skin lesions like psoriasis on the dorsal area of Balb/c and C57 mice. The mice's body weight, skin thickness, and psoriasis area and severity index (PASI) were assessed weekly. SD rats were used in the pharmacokinetics study and the contents of berberine and baicalin were determined. Results The PASI scores and epidermal thickness of mice were markedly decreased after ISDF treatment in both models. ISDF treatment significantly decreased the contents of IL-17A and IL-22 in the serum of IMQ- and IL-23-treated mice. Importantly, ISDF markedly downregulated IL-4, IL-6, IL-1β, and tumor necrosis factor α (TNF-α) gene expression, and the phosphorylation of NF-κB p65, JNK, ERKs and MAPK p38 in IMQ-treated mice. The protein phosphorylation of Jak1, Jak2, Tyk2 and Stat3 was significantly mitigated in the ISDF-treated groups. The absorption of baicalin and berberine of ISDF through the gastrointestinal tract of rats was limited, and their distribution and metabolism in rats were also very slow, which suggested ISDF could be used in the long-term application. Conclusions ISDF has a strong anti-psoriatic therapeutic effect on mouse models induced with psoriasis through IMQ and IL-23, which is achieved by inhibiting the activation of the Jak/Stat3-activated IL-23/Th17 axis and the downstream NF-κB signalling and MAPK signalling pathways. ISDF holds great potential to be a therapy for psoriasis and should be further developed for this purpose.